P0191USE OF CLINICAL FRAILTY SCALE IN PATIENTS WITH CHRONIC KIDNEY DISEASE STAGE 4/5. (6th June 2020) - Wong, Wan Shun; Manssouri, Amin; Robb, James; Cousland, Zoe; Dingwall, Karen; Brennan, Annemarie
Abstract: Background and Aims: Frailty and comorbidity have been shown to predict mortality in end stage renal failure patients. This knowledge can help inform patients and clinicians when undertaking the joint decision-making process regarding the management of advanced renal disease. This project sets out to record the serial and net frailty scores of patients with stage 4 and 5 kidney disease and study the change of frailty score in association with mortality and patient's preferred modality of renal replacement therapy (RRT). Method: All patients followed up in Low Clearance Clinic with eGFR <30ml/min/1.73m 2 were identified from West of Scotland Electronic Renal Patient Record (SERPR). Biochemical data, patient's preferred modality of RRT, clinic/admission records were extracted from SERPR and Clinical Portal. Rockwood Clinical Frailty Scale (CFS) was used to determine patients' degree of frailty (1 being fittest and 9 being frailest). Patient's CFS was reviewed by our Low Clearance Nurse Specialists at 4-monthly interval over a 12-month period. Frailty score was not repeated once patient commenced RRT. Results: 125 patients with CKD stage 4 and 5 had a baseline CFS in April 2018. 54.4% were female and median age was 66 years old. 40.8% patients had a diagnosis of diabetes. Table 1 shows the demographics for patients with baseline CFS 1-3 (not frail), 4-5 (mild frailty) and 6-9 (moderate – severe frailty) respectively. RRT was planned for 82.8% of patients with CFS1-3 (63.3% HD, 36.7 PD), 52.1% of patients with CFS 4-5 (96.0% HD, 4.0% PD) and 36.8% patients with CFS 6-9 (100% HD, 0% PD). 29.2% of patients with CFS 4-5 and 47.4% of patients with CFS 6-9 were for conservative care. 1-year mortality for patients with CFS 1-3, 4-5 and 6-9 was 1.7%, 18.8% and 26.3% respectively. A total of 362 CFS were recorded over the 12-month period (125 at month 0, 88 at month 4, 80 at month 8 and 69 at month 12). 49 changes in CFS were noted in 37 patients. 34 patients had a net deterioration of CFS by the end of month 12. Figure 1 shows the changes in patients' CFS at 4-monthly interval and the net changes by the end of 12-month follow up. Four patients changed their RRT planning from dialysis to conservative care and they all had a deterioration of CFS. Comparing the patients with deterioration of CFS against those without, they had similar number of hospital admissions and clinic appointments and appear to have no association with having the diagnosis of diabetes. However, patients with deterioration of CFS had higher rate of death (14.3% vs 4.7%) and higher likelihood to change their preferred modality of RRT (8.6% vs 4.7%). Conclusion: Frailty is common among patients with advanced CKD and is associated with significant mortality rate. Serial assessment of frailty score is helpful in monitoring patients' physical and functional status. Consistently high or deteriorating frailty score may correlate with higher mortality and this should trigger a review of their suitability for RRT, and consideration of anticipatory care planning.